Issues of Human Resource Management 2017
DOI: 10.5772/67609
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Employee Motivation in Slovakia and Czech Republic

Abstract: The aim of the chapter is to compare the level of employee motivation in enterprises in Slovak and the Czech Republic. Sampling unit consists of 4444 respondents from Slovakia and 2312 from the Czech Republic. Following our outcomes, we can state that the most important motivation factors are mostly identical in both countries; however, there is a slight difference in the order of their importance. Motivation factors relating to financial reward are the most important for employees in the Czech Republic. Basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It can be summarized that the current situation in higher education is characterized by a large number of different tertiary education institutions, whereas the emphasis on their quality is growing, which is influenced by a wide range of factors that influence students' motivation [31]. In terms of international comparison, the quality of these institutions varies.…”
Section: Discussionmentioning
confidence: 99%
“…It can be summarized that the current situation in higher education is characterized by a large number of different tertiary education institutions, whereas the emphasis on their quality is growing, which is influenced by a wide range of factors that influence students' motivation [31]. In terms of international comparison, the quality of these institutions varies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, such as [22][23][24], sought to understand how subjective and behavioral aspects influence people's motivation in their organizational environments.…”
Section: Motivation In Public Servantsmentioning
confidence: 99%
“…When choosing motivational factors, the patterns of cultural differences that predict motivational preferences must be taken into account [34] since the motivational needs of employees from different countries are not the same, despite the fact that they may be regionally close. Research indicates that significant differences in motivational needs have been identified in different countries [35].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%